PENGARUH BIAYA TRANSPORTASI DAN BIAYA PEMASARAN TERHADAP LABA BERSIH PADA PT. SINAR ANDESTO MANDIRI LOGISTIK - Amran, Kiagus Muhammad; Diawati, Prety; Lubis, Nur Iqra Putri (LAND JOURNAL, 2025)
Transportation is a business or activity by carrying goods, passengers from one place to another. Efforts to market products, both goods or services, using planning and systematic methods so that they can increase the number of sales are called marketing. Net profit is the amount of difference between income exceeding expenses (expenses). The study aims to explain "The Effect of Transportation Costs and Marketing Costs on Net Profit at PT. Sinar Andesto Mandiri Logistik". This research was conducted using quantitative methods, secondary data types with associative hypothesis taking. The relationship used in this study is a causal relationship. The population in this study was 264 monthly profit and loss financial reports from the period 2002-2023. This study used the Nonprobability Sampling sampling technique with purposive sampling technique. The data analysis techniques used are normality test, product moment analysis, multiple correlation analysis, multiple linear regression analysis, coefficient of determination, partial test (t), simultaneous test (F). The results of the t-test conducted using IBM Statistic SPSS Version 27, showed that transportation costs partially affected net profit and marketing costs partially did not affect net profit. The results of the F test show that transportation costs and marketing costs simultaneously or together have a significant effect on net profit.